An overview on the factors affecting enzymatic saccharification of lignocellulosic biomass into fermentable sugars - Woo, Wen Xuan; Tan, Jian Ping; Wu, Ta Yeong; Yeap, Swee Keong; Indera Luthfi, Abdullah Amru; Abdul Manaf, Shareena Fairuz; Jamali, Nur Syakina; Hui, Yew Woh (Walter de Gruyter GmbH, 2023)
Lignocellulosic biomass (LCB) is a widely available and sustainable energy resource that can be directly or indirectly converted to biofuels and value-added bioproducts. In such LCB conversion, enzymatic saccharification is commonly regarded as a green alternative to chemical hydrolysis due to less energy-intensive, less toxic, and more environment-benign for efficient fermentable sugar recovery. However, enzymatic saccharification faces substantial challenges, since the complex polymeric matrices of LCB necessitates a variety of enzymes for complete and adequate saccharification. Empirical evidence on enzymatic saccharification has paved the way for optimizing the processes and design for enhancing the performance in LCB. This review examines the enzymatic saccharification of LCB, focusing on the important parameters affecting the process, such as pH, temperature, agitation, enzyme/substrate loading, residence time, and the enzymes required to degrade various LCB components. Various strategies have been reported to improve the performance in saccharification and to address the non-productive adsorption of enzymes. A preliminary economic competency valuation of enzymederived fermentable sugars is proposed. Wheat straw, sugarcane bagasse and corn stalk appear, in this case, to be the most economic competent LCBs for commercial enzyme-derived fermentable sugar production. Lastly, practical challenges and future research directions on the enzymatic saccharification of LCB are discussed.